Teaching And Self-Directed Learning - Alangaram, T.Motcha; Florence, T. Bella; Florence, A.Saravanan; P. Elavarasu,; R. Portia, (International Journal of Psychosocial Rehabilitation, 2020)
Teaching needs to be considered as a profession. It has been argued that each profession should have a particular set of values. Teaching is a form of public service. It requires teacher’s expert knowledge and specialized skills, maintained through rigorous and continuing study. It needs a sense of personal and corporate responsibility for the education and welfare of the pupils. The responsibility of the teachers is to give effective and qualitative improvement in the entire education system and the standard of a Nation. Teaching profession may be defined as an occupation which requires specialized knowledge and advanced learning. Teaching profession is not only an occupation but also performing a crucial social function. Teaching profession is governed by ethical considerations, popularly known’s professional ethics. Self- Directed learning is one of the best methods of learning provide the students to the necessary competencies to become lifelong learners, Self- Directed learning is a skill and it is one of the concept of learning methods in modern day. It provides the experience that students needed to be guided for their own learning method. It teaches them to be a successful learner in life. Self- Directed learning ends not in exercises but in action beyond the class room. Teacher does not teach so much as they direct themselves by empowering them. Self- Directed learning students not closely dependent with other students and adults but they act independently. Self- Directed learning cultivates student’s interests, applies their strengths and equips them for success. Such features enable the teacher to adapt the program to every students to become more self-confident. It is also an independent method of learning, auto didacticism and self learning. It is controlled and managed by the learners’ themselves.